Kebijakan Luar Negeri Turki: Kesepakatan Turki kepada Rusia dalam Mendirikan Pusat Gabungan Turki-Rusia Pasca Konflik Nagorno- Karabakh - Falentinoris Yubilio Wiku; Ika Riswanti Putranti; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The Nagorno-Karabakh conflict, which has become a legacy of the Soviet Union, broke out again on September 27, 2020. This conflict involved Armenia and Azerbaijan, and attracted the attention of international actors, such as Turkey and Russia. The Nagorno-Karabakh conflict lasted for more than six weeks which culminated in a ceasefire agreement signed by Armenia, Azerbaijan and Russia on November 9, 2020. In order to oversee the implementation of this ceasefire agreement, Turkey signed an agreement with Russia to establish a Joint Turkey-Russia Center in November 10, 2020. The purpose of this study is to reveal why Turkey made an agreement with Russia to establish a Joint Turkey-Russia Center in Azerbaijan after the Nagorno-Karabakh conflict (2020). The method used in this research is an explanatory-qualitative approach. This study uses Walter Carlsnaes' Foreign Policy Theory as a theoretical framework. The findings of this study reveal that Turkey made an agreement with Russia in establishing the Turkey-Russia Joint Center because of Turkey's dependence on Russia and the ineffectiveness of co-chairs OSCE Minsk Group , as well as the influence of Turkey's foreign policy doctrine which then prompted Turkish President Recep Tayyip Erdoğan to take strategic role with Russia as well as intermediary for the peace process for Azerbaijan after the Nagorno-Karabakh conflict.